Maternal Western Style Diet Increases Susceptibility to Chemically-Induced Mammary Carcinogenesis in Female Rats Offspring - Lopes, Gisele A. D. [UNESP]; Fan, William Y. C. [UNESP]; Ciol, Heloisa [UNESP]; Bidinotto, Lucas T.; Rodrigues, Maria Aparecida Marchesan [UNESP]; Barbisan, Luis Fernando [UNESP] (Routledge Journals, Taylor & Francis Ltd, 2014)
The present study investigated whether maternal exposure to western style diet (WD) increases susceptibility to mammary carcinogenesis induced by N-methyl-N-nitrosourea (MNU) in female offspring. Pregnant female Sprague-Dawley rats received WD diet or control diet from gestational day 12 until postnatal day (PND) 21. At PND 21, female offspring received a single dose of MNU (50mg/kg body weight) and were fed chow diet until PND 110. Mammary gland structures were assessed on whole-mount preparations in the offspring at PND 21, and tumor morphology was examined at PND 110. Immunohistochemical analysis for cell proliferation (PCNA), apoptosis (cleaved caspase-3) and estrogen receptor alpha (ER-alpha) was performed in mammary terminal end buds (TEBs) at PND 21, and PCNA, ER-alpha, and p63 analysis in mammary tumors at PND 110. Maternal WD intake induced a significant increase in the number of TEBs (P = 0.024) and in PCNA labeling index (P < 0.020) in the mammary glands at PND 21. Tumor multiplicity, tumor weight, and PCNA labeling indexes were significantly higher in the WD offspring than that of the control offspring (P < 0.05). These findings indicate that maternal western style diet potentially enhanced the development of mammary tumors induced by MNU in female offspring, possibly by affecting the mammary gland differentiation.